The Role of Parasite Words in Providing Speech Intention - Ibragimova Umida Yuldashevna (Genius Journals, 2022)
In ensuring the culture of speech, the role of such communicative qualities as purity, correctness, consistency, richness, accuracy, expressiveness, expressiveness is important. Parasitic words, which are considered to be detrimental to the purity of speech, can sometimes serve pragmatic functions. In some speech situations, they are for the speaker one of the main means of achieving the intended goal of speech.
Keywords: Intention; parasitic words; purity of speech; pragmatic tasks